Anguilla anguilla intestinal immune response to natural infection with Contracaecum rudolphii A larvae. Issue 10 (27th January 2016) - Dezfuli, B S; Manera, M; Bosi, G; DePasquale, J A; D'Amelio, S; Castaldelli, G; Giari, L
Abstract: The European eel, Anguilla anguilla, is a major warm‐water fish species cultured in North and South Europe. Seventy‐one A. anguilla collected between 2010 and 2015 from the Comacchio lagoons were examined. Fish were infected and damaged by larvae (L3) of the nematode Contracaecum rudolphii A, which were encapsulated within the thickness of the intestinal wall and within the external visceral peritoneum (serosa). Conspicuous granulomas, visible at sites of infection, were arranged in a trilayer, formed by a series of concentric whorls. The cells involved in the immune response and their distribution in the granuloma layers were assessed by immunohistochemical, immunofluorescence, and ultrastructural techniques. The outer part of the granuloma contained macrophages, macrophage aggregates, and mast cells (MCs) scattered among fibroblasts. This layer was vascularized, with degranulation of MCs occurring in close proximity to the capillaries. The middle layer was rich in MCs and fibroblasts. The inner layer, closest to the parasite larva, consisted mainly of dark epithelioid cells, some of which were necrotic. Non‐necrotic epithelioid cells formed desmosomes between themselves or with fibroblasts. Within the granulomas, numerous cells of different types were positive to proliferative cell nuclear antigen antibody, indicating a high degree of cellular proliferation around the larvae.